Challenges and Specificities of Battlefield Archaeology in Argentina: The Case of Cepeda Battlefield, 1859 - (:unkn) unknown (Conference Proceedings: Fields Of Conflict, 2016)
The battle of Cepeda, 1859, was one of the high points in the crucial confrontation between the Argentine Confederation and the then rebellious Buenos Aires Province, which shaped the process of modern nation state building. Whereas the confederate army commanded by president Justo J. Urquiza defeated the provincial army led by Bartolomé Mitre, this victory would not be decisive and more fighting would follow until Buenos Aires’ definitive triumph in 1861. The battle has only been studied by historians, using the contradictory commanders’ battle reports. This paper presents the archaeological research on the battlefield. We discuss methods, finds, and interpretations, but also use this case study to address three major issues that differentiate this battlefield study from contemporary European and North American cases: 1) Heterodox battle tactics, which combined Napoleonic style tactics for infantry and artillery, with a locally developed emphasis on irregular and light cavalry; 2) A lack of written sources on both weapons employed and specific details of the battle; 3) Landscape transformations that significantly altered the original battle ground. As a whole, these issues - a widespread occurrence in Argentine XIXst century battles - challenge the development of battlefield studies and pose limitations to its interpretive potential.
Keywords: Battle of Cepeda; Battlefield Archaeology; Argentina; 1859; Challenges